Datura stramonium Leaves Mucilage Aided Buccoadhesive Films of Aceclofenac using 32 Factorial Design with Design-Expert Software - Ahad, Hindustan Abdul; Chinthaginjala, Haranath; Priyanka, Manchikanti Sai; Raghav, Dasari Rahul; Gowthami, Madana; Jyothi, Varam Naga (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim and Objectives: The main motto of this work was to search the additive effect of Datura stramonium leaves mucilage in the making of buccoadhesive film by taking Aceclofenac as a model drug. Materials and Methods: Nine formulations of buccal films were made using Carbopol 934 P and varying proportions of Ethyl Cellulose and D. stramonium leaves mucilage. The films were judged for compatibility studies and physical constraints including Aceclofenac content and discharge. Results: Among the films F-9 containing 1:1 of Aceclofenac and ethyl cellulose; and 1:0.5 ratios of Aceclofenac: D. stramonium leaves mucilage was found to have good Mucoadhesion time (10.5±0.1h) and Bioadhesive strength (5.5±0.2g). The formulation F2 showed the highest % release i.e., 92.85% up to 8 h. Conclusion: The study resolved that buccoadhesive drug delivery system for Aceclofenac with ethyl cellulose aided with D. stramonium leaves mucilage meets the ideal requirement for buccal devices is an efficient approach to surpass the hepatic first-pass metabolism and increase bioavailability.
Keywords: Aceclofenac; Mucilage; Factorial design; Buccal Film; Bio adhesive strength